(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to investigate the impact of the common identity strategy on the academic achievement in the Arabic language subject among second-grade middle school students. The researcher adopted the experimental method as it is suitable for the nature and objective of the study. The researcher identified the research population as second-grade middle school students in daytime boys’ intermediate and secondary schools affiliated with the Directorate General of Education in Thi Qar Governorate for the academic year (2023-2024). The researcher selected a random sample of 64 students from Al-Wameedh Secondary School for Boys, under the Directorate of Education in Thi Qar. They were randomly assigned to two groups (experimental and control), with 31 students in the experimental group and 33 in the control group. The researcher taught the same material to both research groups, starting on Monday, October 22, 2023, and ending on Monday, January 8, 2024, with two sessions per week for each group. The experiment continued for a full semester. The researcher prepared an achievement test consisting of 36 items distributed on objective questions, administered to both experimental and control research groups at the end of the experiment. The test was characterised by validity, reliability, and objectivity. The researcher analyzed the research data and results using the Statistical Package for the Social Sciences (SPSS) and the following equations: independent samples t-test, chi-square, difficulty index, discrimination index, effectiveness of alternatives, Kuder-Richardson Formula 20, Cooper Formula, and Cronbach’s Alpha Formula. The research yielded the following results: the performance of students in the experimental group surpassed that of students in the control group